Effect of speed on relationships between impairment side, breathing laterality and coordination symmetry in Paralympic swimmers - Seifert, L.; Létocart, A.; Guignard, B.; Regaieg, M. A. (Sports Biomechanics, 2025)
This study questioned the influence of unilateral physical impairment on controlling inter-limb coordination, notably the coordination symmetry. We investigated whether unilateral physical impairment and unilateral breathing preference led to motor coordination asymmetry in eleven elite Para swimmers during 10 times 25 m in front crawl incremented in speed. Multicamera video system and five inertial measurement units were used to assess arm and leg phases and to compute symmetry of arm coordination and of arm-leg synchronisation. Hierarchical cluster analysis was used to classify the different profiles of relationships between impairment, breathing and motor coordination symmetry. Unilateral impairment led to asymmetric arm coordination (~83% of time, mostly at fast speeds), which always occurred to the side of the affected limb and which was associated to the preferential breathing side (~53% of time), while arm-leg synchronisation remained mainly symmetric (66.7 to 86.1% of time). It could be advised to assess the influence of impairment side and breathing side preference on motor coordination symmetry (1) to understand how the Para swimmers functionally adapt to their impairment, (2) to ensure that the unaffected limb generates great propulsion, and (3) to ensure that breathing does not impair propulsion nor increase motor coordination asymmetry.